Circular economy and durability in geopolymers ceramics pieces obtained from glass polishing waste - de Azevedo, Afonso R. G.; Teixeira Marvila, Markssuel; Barbosa de Oliveira, Leandro; Macario Ferreira, Weslley; Colorado, Henry; Rainho Teixeira, Silvio [UNESP]; Mauricio Fontes Vieira, Carlos (Wiley, 2021)
The development of new building materials based on alkaline activation technology is very promising, mainly linked to products that need significant technological properties and durability due to their adverse service conditions and environmental exposure. The objective of this research was to evaluate the development of a circular economy within the scope of durability of ceramic pieces incorporating glass polishing waste aimed at the production of roof tiles, obtained by the geopolymerization process. Two methodologies to evaluate the sample's durability were studied: wetting and drying cycles; and exposure to salt spray; both simulating conditions that tiles typically face in normal conditions. Prismatic specimens were made with an alkaline solution/(metakaolin + waste) ratio = 0.26; a SiO2/Al2O3 molar ratio = 3.5, 4, and 4.5; and with ambient and thermal cure at 7 days. Samples were evaluated in their mechanical strength, mass loss, and water absorption. Results showed that the SiO2/Al2O3 = 4.0 ratio with thermal curing had the best behavior in aggressive conditions, and therefore, this formulation can be used for the production of tiles.
Keywords: ceramic roof tiles; circular economy; geopolymers; glass waste